Ethical elements in priority setting in nursing care: A scoping review - Suhonen, Riitta; Stolt, Minna; Habermann, Monika; Hjaltadottir, Ingibjörg; Vryonides, Stavros; Tonnessen, Siri; Halvorssen, Kristin; Harvey, Clare; Toffoli, Luisa; Scott, P. Anne (My University, 2018)
Background Nurses are often responsible for the care of many patients at the same time and have to prioritise their daily nursing care activities. Prioritising the different assessed care needs and managing consequential conflicting expectations, challenges nurses’ professional and moral values. Objective To explore and illustrate the key aspects of the ethical elements of the prioritisation of nursing care and its consequences for nurses. Design, data sources and methods A scoping review was used to analyse existing empirical research on the topics of priority setting, prioritisation and rationing in nursing care, including the related ethical issues. The selection of material was conducted in three stages: research identification using two data bases, CINAHL and MEDLINE. Out of 2024 citations 25 empirical research articles were analysed using inductive content analysis. Results Nurses prioritised patient care or participated in the decision-making at the bedside and at unit, organisational and at societal levels. Bedside priority setting, the main concern of nurses, focused on patients’ daily care needs, prioritising work by essential tasks and participating in priority setting for patients’ access to care. Unit level priority setting focused on processes and decisions about bed allocation and fairness. Nurses participated in organisational and societal level priority setting in discussion about the priorities. Studies revealed priorities set by nurses include prioritisation between patient groups, patients having specific diseases, the severity of the patient’s situation, age, and the perceived good that treatment and care brings to patients. The negative consequences of priority setting activity were nurses’ moral distress, care missing, which impacts on both patient outcomes and nursing professional practice and quality of care compromise. Conclusions Analysis of the ethical elements, the causes, concerns and consequences of priority setting, need to be studied further to reveal the underlying causes of priority setting for nursing staff. Prioritising has been reported to be difficult for nurses. Therefore there is a need to study the elements and processes involved in order to determine what type of education and support nurses require at assist them in priority setting.
Keywords: Ethics; Nurse; Nursing care; Priority setting; Prioritisation; Rationing; Scoping review